Hair cortisol concentration (HCC) as a measure for prenatal psychological distress — A systematic review - Paula Mustonen; Linnea Karlsson; Noora M. Scheinin; Susanna Kortesluoma; Bárbara Coimbra; Ana João Rodrigues; Hasse Karlsson (Elsevier, 2022)
Prenatal environment reportedly affects the programming of developmental trajectories in offspring and the modification of risks for later morbidity. Among the increasingly studied prenatal exposures are maternal psychological distress (PD) and altered maternal hypothalamus-pituitary-adrenal (HPA) axis functioning. Both prenatal PD and maternal short-term cortisol concentrations as markers for HPA axis activity have been linked to adverse child outcomes and it has been assumed that maternal PD affects the offspring partially via altered cortisol secretion patterns. Yet, the existing literature on the interrelations between these two measures is conflicting. The assessment of cortisol levels by using hair cortisol concentration (HCC) has gained interest, as it offers a way to assess long-term cortisol levels with a single non-invasive sampling. According to our review, 6 studies assessing the associations between maternal HCC during pregnancy and various types of maternal PD have been published so far. Measures of prenatal PD range from maternal symptoms of depression or anxiety to stress related to person's life situation or pregnancy. The aim of this systematic review is to critically evaluate the potential of HCC as a biomarker for maternal PD during pregnancy. We conclude that HCC appears to be inconsistently associated with self-reported symptoms of prenatal PD, especially in the range of mild to moderate symptom levels. Self-reports on PD usually cover short time periods and they seem to depict partly different phenomena than HCC. Thus, methodological aspects are in a key role in future studies evaluating the interconnections across different types of prenatal PD and maternal HPA axis functioning. Further, studies including repetitive measurements of both HCC and PD during the prenatal period are needed, as timing of the assessments is one important source of variation among current studies. The significance of prenatal HCC in the context of offspring outcomes needs to be further investigated.